A engrenagem fílmica e seus efeitos à deriva em um movimento de sentidos e sujeitos na materialidade discursiva significante - Pinto, Denise Machado (2016)
In this thesis, we aim at understanding how the discourse of and in the materiality of cinema works from what we define as (self)visualization of the subject in between places. For such, we ask ourselves about the subject present in the process of movie creation and visualization and try to understand how the relation between subject and process happens. Our research corpus is composed by the movies Maluco de Estrada II - Cultura de BR (2015) and Geração Bendita (1971), with which we performed 3 (three) discourse compositions in order to observe how memory works, through interdiscourse operation, of the paraphrastic process and the movement of subjects in their gestures to signify themselves. Among signifiers that extend to working in different conditions of production, subjects (re)signify themselves and keep the public space as point of conflict in the significant discourse materiality, also a place of sharing of the sensitive (RANCIÈRE, 2005 [2000]). Finally, it is relevant to mention that this study is based on Pêcheux s Discourse Analysis, which considers the conditions of discursivity production and how ideology and the unconscious act as founders for the developed analyses.